2012
DOI: 10.1021/np300067m
|View full text |Cite
|
Sign up to set email alerts
|

Indole Alkaloids from Geissospermum reticulatum

Abstract: Ten indole alkaloids were isolated from Geissospermum reticulatum, seven (1-7) from the leaves and three (8-10) from the bark. Seven were aspidospermatan-type alkaloids (1-3, 5-9), including four (5-8) with a 1-oxa-3-cyclopentene group in their molecule, which we named geissospermidine subtype. Compounds 1-3, 5-8, and 10 had not been reported previously as natural products, while 4 and 9 were the known alkaloids O-demethylaspidospermine and flavopereirine. Their structures were determined by spectroscopic tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 35 publications
0
21
0
2
Order By: Relevance
“…Various alkaloids presented anti-leishmanial activity [14][15][16]. In the present study we selected two species of this family, but any alkaloid was detected or isolated.…”
Section: Discussionmentioning
confidence: 99%
“…Various alkaloids presented anti-leishmanial activity [14][15][16]. In the present study we selected two species of this family, but any alkaloid was detected or isolated.…”
Section: Discussionmentioning
confidence: 99%
“…It contains the alkaloid flavopereirine (also called PB-100), as well as many other kinds of indole and b-carboline alkaloids (Puiseux et al, 1959;Reina et al, 2012;Steele et al, 2002). According to anecdotal reports and some inconclusive evidence, flavopereirine or Pao may be of benefit for the treatment of malaria, cancer (including prostate cancer, glioblastoma and leukemia), HIV/AIDS, herpes simplex and hepatitis C (Beljanski & Beljanski, 1982;Beljanski et al, 1993;Bemis et al, 2009;Reina et al, 2012;Steele et al, 2002). However, Pao is commonly administered together with other herbal remedies, including ginkgo (Ginkgo biloba) and the indole alkaloid alstonine, which may have antipsychotic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Steele et al (2002) reported isolation of the three indole alkaloids and a b-carboline alkaloid flavopereirine from the bark of Geissospermum sericeum and their antiplasmodial activities. Reina et al (2012) reported seven indole alkaloids from the leaves and three from the bark of Geissospermum reticulatum and the antiparasitic activities of both the extract and each alkaloid. Mbeunkui et al (2012) isolated a new indole alkaloid along with four known indole alkaloids from the bark of Geissospermum vellosii and described their antiplasmodial activities.…”
Section: Introductionmentioning
confidence: 99%
“…There are some evidence showing that Geissospermum species demonstrate anti-malarial, antibacterial and nociceptive activities [1,7,8]. In our previous publication we reported that infusions, tinctures and extracts of Geissospermum reticulatum bark have potential to be used as good sources of bioactive compounds and exhibit antioxidant, cytotoxic and anti-proliferative properties [9].…”
Section: Introductionmentioning
confidence: 98%